RELATIONSHIP BETWEEN TOURISM AND ECONOMIC GROWTH IN MEDITERRANEAN BASIN COUNTRIES (Third Sector Social Economic Review, 2025)
The countries of the Mediterranean basin receive about a third of the world's incoming tourists. This situation underlines the importance of the Mediterranean in world tourism. Because of this importance, the tourism sector is expected to have a positive impact on the economic growth of the countries. It is important to examine the impact of tourism on the economies of this region, which is important for world tourism. This study examines the impact of tourism on economic growth in 12 Mediterranean countries. The econometric method used in the study is ARDL. As a result of the study, it was found that there is a long-run relationship between tourism and economic growth in countries other than Malta and Greece. When evaluating the long-run coefficients, the impact of tourism on economic growth is positive in all countries. The results are statistically significant for France, Spain, Israel, Egypt and Türkiye. In the short term, tourism has a positive effect on economic growth in Italy, but a negative effect in Israel. The results obtained are in line with economic theory and literature. The results indicate that the tourism-based growth hypothesis is valid in the Mediterranean countries. For the sake of sustainability, it is important to develop national and international economic policies that will further increase the positive impact of tourism on economic growth in the Mediterranean countries and support improvements that will contribute to the social, political and economic stability of the region.
Keywords: Economic Growth; Tourism; ARDL; Mediterranean Basin